FEASIBILITY OF BIOLOGY TEXTBOOK CLASS X SENIOR HIGH SCHOOL BASED ON INQUIRY ON THE TOPIC OF THE SCOPE OF BIOLOGY TO TRAIN SCIENCE PROCESS SKILLS - Dhewi, Endha Sukma; Rachmadiarti, Fida (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2018)
Textbooks have to fulfill the demands of curriculum 2013 objectives of developing higher order thinking skills and accordance with the demands of 21st century skills, so the research on the development of textbooks in accordance with the demands of the curriculum 2013 objectives and 21st century skills is needed. The purpose of this research was to describe feasibility of biology textbook based inquiry developed on the topic of the scope of biology for class X senior high school. The type of this research was development research. The method used in this research was 4D development model. The 4D development stages include define i.e. analyze curriculum, concepts, tasks, students and learning objectives. On the design stage i.e. compile textbook. On the develop stage i.e. validation and the trials of textbook, and the disseminate stage in this research was not implemented. The collected data covered validity and practicality of textbook. The validity of textbook based on advisability in contents, linguistic, and presentation. The practicality of textbook based on readability of textbook and activity of feature process skills. The trials of textbook based inquiry were held to 16 students class X MA Negeri Mojosari, Mojokerto. The data were qualitativeÂ  descriptively analyzed. The interpretation of the average criteria score of validation was 82,06 that included valid category. The readability of textbook on level 10, hence inquiry textbook was appropriate for used by students class X senior high school. The inquiry-based textbook was able to train science process skills. The result showed that the textbook was valid and practical.Â Keywords: textbook, inquiry, the scope of biology.